Solution of the Problem of Natural Gas Storages Creating in Gas Hydrate State in Porous Reservoirs - Nail G. Musakaev; Marat K. Khasanov (Mathematics, 2020)
Underground gas hydrate storage of natural gas is a rather promising way of creating underground storage facilities for hydrocarbon raw materials in porous reservoirs. This paper presents a solution to the problem of the formation of CH 4 hydrate in a porous medium during the injection of methane into a reservoir at a temperature lower than the initial temperature of the reservoir. Self-similar solutions of the problem in axisymmetric approximation are given, describing the pressure and temperature distribution in separate reservoir regions at the formation of gas hydrate on the frontal surface. On the basis of the method of sequential change of stationary states, an analytical solution was obtained, which allowed us to determine the position of the methane hydrate formation boundary depending on different parameters for any moment of time. The limits of the applicability of the proposed model are also given. Thus, the analysis of the calculation results showed that the constructed solution allows one to sufficiently and accurately determine the values of parameters at the frontal surface for a highly permeable medium ( k 0 > 10 −13 m 2 ). It was proved that in the case of a highly permeable medium, the methane hydrate formation intensity will be limited by convective heat dissipation during hydrate formation.